Neuronal Nitric Oxide Synthase in Neural Stem Cells Induces Neuronal Fate Commitment via the Inhibition of Histone Deacetylase 2 - Jin, Xing; Yu, Zhang-Feng; Chen, Fang; Lu, Guang-Xian; Ding, Xin-Yuan; Xie, Lin-Jun; Sun, Jian-Tong (Frontiers in Cellular Neuroscience, 2017)
Active adult neurogenesis produces new functional neurons, which replace the lost ones and contribute to brain repair. Promoting neurogenesis may offer a therapeutic strategy for human diseases associated with neurodegeneration. Here, we report that endogenous neuronal nitric oxide synthase (nNOS) for neural stem cells (NSCs) or progenitors positively regulates neurogenesis. nNOS repression exhibits significantly decreased neuronal differentiation and nNOS upregulation promotes neurons production from NSCs. Using a quantitative approach, we show that instructive effect, that is instruction of NSCs to adopt a neuronal fate, contributes to the favorable effect of endogenous nNOS on neurogenesis. Furthermore, nNOS-mediated instruction of neuronal fate commitment is predominantly due to the reduction of histone deacetylase 2 (HDAC2) expression and enzymatic activity. Further investigation will be needed to test whether HDAC2 can serve as a new target for therapeutic intervention of neurodegenerative disorders.